The role of glutamate receptors in the regulation of the tumor microenvironment - Koda, Stephane; Hu, Jing; Ju, Xiaoman; Sun, Guowei; Shao, Simin; Tang, Ren-Xian; Zheng, Kui-Yang; Yan, Juming (Frontiers in Immunology, 2023)
Glutamate, as one of the most important carbon sources in the TCA cycle, is central in metabolic processes that will subsequently influence tumor progression. Several factors can affect the expression of glutamate receptors, playing either a tumor-promoting or tumor-suppressor role in cancer. Thus, the activation of glutamate receptors by the ligand could play a role in tumor development as ample studies have demonstrated the expression of glutamate receptors in a broad range of tumor cells. Glutamate and its receptors are involved in the regulation of different immune cells’ development and function, as suggested by the receptor expression in immune cells. The activation of glutamate receptors can enhance the effectiveness of the effector’s T cells, or decrease the cytokine production in immunosuppressive myeloid-derived suppressor cells, increasing the antitumor immune response. These receptors are essential for the interaction between tumor and immune cells within the tumor microenvironment (TME) and the regulation of antitumor immune responses. Although the role of glutamate in the TCA cycle has been well studied, few studies have deeply investigated the role of glutamate receptors in the regulation of cancer and immune cells within the TME. Here, by a systematic review of the available data, we will critically assess the physiopathological relevance of glutamate receptors in the regulation of cancer and immune cells in the TME and provide some unifying hypotheses for futures research on the role of glutamate receptors in the immune modulation of the tumor.